Cognitive barriers in learning: impact of digitalization and global competencies on stress resilience and attention - Nurzhanat Shakirova; Nursultan Bakanov; Karlygash Muzdybayeva; Gulnara Rizakhojayeva (Institute of Advanced Engineering and Science, 2026)
One of the key cornerstones for educators is addressing various communicative barriers in student learning. The aim of this study was to determine the impact of a virtual reality (VR)-based model on several cognitive barriers, specifically focusing on students’ stress resilience and attention levels. A sample from two universities was utilized: Abai Kazakh National Pedagogical University and First Moscow State Medical University named after I.M. Sechenov, comprising a total of 138 students. The experimental component involved the VR program “sustainable development and cognitive barriers” (SDCB). The study examined changes in two barriers related to stress and inattention. The results indicate a positive impact. The pre-intervention stress resilience level (43.56) and the post-intervention level (9.02) show a significant difference with a positive trend at p=0.001. A similar trend is observed in the context of attentiveness characteristics: p=0.000. Considering the stratification approach, differences within the experimental group before and after the intervention were also analyzed based on specific characteristics. No significant relationships were found between the strata and the variable. This article will be valuable for educators, psychologists, policymakers, and other interested parties.